2021
DOI: 10.3390/cryst11010045
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of Void Nucleation and Early Growth at Incoherent Precipitates: Lattice-Trapped and Dislocation-Mediated Delamination Modes

Abstract: The initial stages of debonding at hard-particle interfaces during rupture is relevant to the fracture of most structural alloys, yet details of the mechanistic process for rupture at the atomic scale are poorly understood. In this study, we employ molecular dynamics simulation of a spherical Al2Cu θ precipitate in an aluminum matrix to examine the earliest stages of void formation and nanocrack growth at the particle-matrix interface, at temperatures ranging from 200–400 K and stresses ranging from 5.7–7.2 GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The atomistic simulation approach is particularly useful in the analysis of the initial phases of void nucleation and the assessment of the accompanying physical phenomena, the experimental capture of which, due to technical difficulties, is troublesome or sometimes even impossible. For instance, Zhao et al [ 52 ], using molecular dynamics (MD) analysis, simulated the separation of a spherical Al 2 Cu θ precipitate in an aluminium matrix. Reaching the atomic level made it possible to distinguish three stages of the early phase of decohesion, namely: a nucleus of excess free volume at the phases’ interface, nuclei growth in the absence of dislocation activity and the emission of Shockley partial dislocations leading to fast microcrack development.…”
Section: Void Nucleationmentioning
confidence: 99%
“…The atomistic simulation approach is particularly useful in the analysis of the initial phases of void nucleation and the assessment of the accompanying physical phenomena, the experimental capture of which, due to technical difficulties, is troublesome or sometimes even impossible. For instance, Zhao et al [ 52 ], using molecular dynamics (MD) analysis, simulated the separation of a spherical Al 2 Cu θ precipitate in an aluminium matrix. Reaching the atomic level made it possible to distinguish three stages of the early phase of decohesion, namely: a nucleus of excess free volume at the phases’ interface, nuclei growth in the absence of dislocation activity and the emission of Shockley partial dislocations leading to fast microcrack development.…”
Section: Void Nucleationmentioning
confidence: 99%
“…In contrast, the void nucleated within the Mg precipitate in the Al-Mg system and propagated into the Al matrix. Recently, Zhao et al [120] suggested that the initial delamination took place with an increase in the displacement of atoms, without the formation of local dislocation structures. This stage, termed as the lattice-trapped delamination process, was followed by the dislocation-assisted growth of the nucleated void.…”
Section: Void Nucleation and Growth Mechanisms At Nano-and Sub-micron...mentioning
confidence: 99%
“…This implies that nucleation is favoured at a higher strain rate, attributing the strain rate sensitivity to the formation of voids. Zhao et al [120] also investigated the effect of temperature and stress on the void formation in FCC Al and demonstrated that the lattice-trapped delamination of the void nucleation was the rate-limiting process.…”
Section: Void Nucleation and Growth Mechanisms At Nano-and Sub-micron...mentioning
confidence: 99%